Multiple Electrolyte and Metabolic Emergencies in a Single Patient - Caprice Cadacio; Phuong-Thu Pham; Ruchika Bhasin; Anita Kamarzarian; Phuong-Chi Pham (Case Reports in Nephrology)
While some electrolyte disturbances are immediately life-threatening and must be emergently treated, others may be delayed without immediate adverse consequences. We discuss a patient with alcoholism and diabetes mellitus type 2 who presented with volume depletion and multiple life-threatening electrolyte and metabolic derangements including severe hyponatremia (serum sodium concentration [SNa] 107 mEq/L), hypophosphatemia (“undetectable,” <1.0 mg/dL), and hypokalemia (2.2 mEq/L), moderate diabetic ketoacidosis ([DKA], pH 7.21, serum anion gap [SAG] 37) and hypocalcemia (ionized calcium 4.0 mg/dL), mild hypomagnesemia (1.6 mg/dL), and electrocardiogram with prolonged QTc. Following two liters of normal saline and associated increase in SNa by 4 mEq/L and serum osmolality by 2.4 mosm/Kg, renal service was consulted. We were challenged with minimizing the correction of SNa (or effective serum osmolality) to avoid the osmotic demyelinating syndrome while replacing volume, potassium, phosphorus, calcium, and magnesium and concurrently treating DKA. Our management plan was further complicated by an episode of significant aquaresis. A stepwise approach was strategized to prioritize and correct all disturbances with considerations that the treatment of one condition could affect or directly worsen another. The current case demonstrates that a thorough understanding of electrolyte physiology is required in managing complex electrolyte disturbances to avoid disastrous outcomes.